Peran Coping Mechanism sebagai Moderator dalam Hubungan Technostress dengan Employee Well-Being pada Remote Workers - Alhamdika, Fikri Alhamdika; Daisy Leries, Frinska; Julia Ilham, Dina; Rahmi, Tuti (Buletin Riset Psikologi dan Kesehatan Mental, 2025)
The rise of digital technology has increased work-related stress, especially for remote workers who rely heavily on digital tools. This study aims to find out whether coping mechanism can help reduce the negative effects of technostress on employee well-being. The hypothesis suggests that while high technostress lowers well-being, effective coping can buffer this impact. This quantitative study involved 210 remote workers in Indonesia and used three main instruments: a technostress scale, a coping questionnaire, and an employee well-being scale. The results show that coping is not only positively related to well-being, but it also weakens the negative effect of technostress. These findings highlight how important it is for remote workers to have good coping mechanism, and how organizations should actively support them to stay mentally healthy in an increasingly digital work environment.